#### Answer

$y' = 1$

#### Work Step by Step

Quotient Rule:
$y=\frac{x^2-a^2}{x-a}$
$y' = \frac{(2x)(x-a)-(x^2-a^2)(1)}{(x-a)^2} = 1$
Division then Power Rule:
$y=\frac{x^2-a^2}{x-a} = \frac{(x-a)(x+a)}{x-a} = x+a$
$y' = 1$

Published by
Pearson

ISBN 10:
0321947347

ISBN 13:
978-0-32194-734-5

$y' = 1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.